Evaluation of Condyle–Fossa Relationships in Adults with Various Skeletal Patterns Using Cone-Beam Computed Tomography - Alice Choi; Jae Hyun Park; Curt Bay; Jong-Moon Chae (Applied Sciences)
This study assessed the condyle–fossa relationships in adults with different skeletal patterns using cone-beam computed tomography (CBCT). A total of 135 adult participants were included in the analysis of the CBCT images. Participants were categorized based on gender, age, race, and skeletal patterns. The measurements of the temporomandibular joint spaces were taken, which include the anterior (AS), superior (SS), posterior (PS), medial (MS), central (CS), and lateral (LS) spaces. Additionally, the dimensions of the condyle were assessed, including mediolateral thickness (MLT), anteroposterior thickness (APT), articular slope (ArS), and the vertical height of the fossa (VHF). These measurements were then compared. The average ratios of AS:SS:PS and MS:CS:LS were 1.00:1.61:1.18 and 1.00:1.15:0.79, respectively. The average values of most measurements were significantly higher in males than in females. The average value of APT was significantly higher in the late age group than in others, but there was no statistical difference according to race. The average values of PS, CS, and LS were significantly higher on the left side than on the right, while the average value of AS was significantly higher on the right side than on the left. The average values of SS, CS, and MLT were significantly higher in hypodivergent than in hyperdivergent skeletal patterns, while the average values did not show any statistical differences based on horizontal skeletal patterns. The average values of SS and CS in the Class II horizontal skeletal group were significantly lower in hyperdivergent individuals compared to other vertical skeletal patterns. In adults, statistical differences in condyle–fossa relationships were observed based on gender, age, sides, and skeletal patterns, but no differences were identified according to race.